Understanding dance/movement therapy: a qualitative study of Chinese parents of children with autism spectrum disorder - Fan, Xing; Ko, Kyung Soon (Frontiers in Psychology, 2025)
IntroductionThis study explored the application of dance/movement therapy (DMT), a therapeutic method originating from the West, in the treatment of children with autism spectrum disorder (ASD) in China. Specifically, it examined how these children’s parents understood and perceived DMT.MethodsA descriptive qualitative research design was employed. Five Chinese parents of children with ASD participated. Data were collected through three sources: videos of sessions, in-depth interviews, and movement interviews. Data analysis involved coding and categorization, resulting in 158 codes, 48 subcategories, and 14 categories.ResultsFive main themes were identified: (1) Facing the Unknown but Willing to Try, (2) Observing Embodied Communication and Emotional Growth, (3) Witnessing an Unexpected Therapeutic Relationship, (4) Seeing Therapy Extend into Daily Life, and (5) Reflecting on Parenting and Family Changes.DiscussionThe findings provide foundational insights into how parents of children with ASD perceive DMT in the Chinese cultural context. These results highlight the potential for implementing and promoting DMT in China based on parental perspectives.